The uneven and combined development of class forces: migration as combined development. Issue 3 (2nd July 2016) - Evans, Jessica
Abstract: One of the more interesting and potentially powerful developments within Marxist approaches to the field of international relations has been the recent revival of Trotsky's concept of uneven and combined development (UCD). However, it appears that there have been very few attempts within this literature to specify in concrete terms what is meant by mechanisms of 'combination'. Failing this, UCD runs the risk of falling into triviality. To this end, this article suggests that migration has historically functioned as a crucial element of combined development, contributing to the uneven incorporation of non-capitalist societies into the remit of a developing world capitalist market. As illustration, I take settler-colonial development and the Great Atlantic Migrations as my focal point, drawing out a comparative study of Argentine and Canadian wheat production in the late nineteenth century. In positing these migrations as mechanisms of combined development I suggest that such were the means by which both European capitalism developed extensively and intensively and New World societies were subjected to the 'pressures of backwardness', compelled to transform their own social relations of production.